Suspicion at seven - Purser, Ann (Purser, Ann. Lois Meade mysteries, 2014)
"Lois Meade has done enough buffing and polishing over the years with her cleaning business, New Brooms, to know that all that glitters is not gold. So when a bag of costume jewellery is the main clue in a murder, she has a strong suspicion that appearances may be deceiving... After a woman is discovered in the Mill House Hotel, strangled with a silver necklace beside a bag filled with faux silver, gold and pearls, costume jewelry dealer Michael Black seems like the obvious suspect. But Lois knows Michael's wife, who runs a baker's shop near the hotel, and can't believe her husband could be a killer. Plus, Michael has an airtight alibi. Nevertheless, Michael--who prefers to go by Michel, a name as fake as his gems--is no angel. It appears he's running a pyramid scheme, and Lois's mother is getting sucked in. Could the murder have anything to do with his unscrupulous business practices? As Inspector Cowgill and Lois hope the bling may shine a light on the killer, the discovery of a second body on the old waterwheel in the hotel may be grist for the mill in solving the murder--if they can manage to catch the culprit without getting the runaround"--